A novel process to recycle spent LiFePO4 for synthesizing LiFePO4/C hierarchical microflowers. (1st February 2016) - Bian, Doucheng; Sun, Yonghui; Li, Sheng; Tian, Yuan; Yang, Zeheng; Fan, Xiaoming; Zhang, Weixin
Highlights: A novel process has been demonstrated to recycle spent LiFePO4. FePO4 ·2H2 O and LiH2 PO4 were recovered separately from spent LiFePO4 . LiFePO4 /C hierarchical microflowers were derived of the FePO4 ·2H2 O precursor. The re-synthesized LiFePO4 /C shows high electrochemical performance as cathode materials. Abstract: A novel process has been demonstrated to recycle LiFePO4 from spent lithium-ion batteries. The spent LiFePO4 cathode materials were leached by phosphoric acid (H3 PO4 ) solution and followed by subsequent heat treatment to obtain FePO4 ·2H2 O hierarchical microflowers. Furthermore, new LiFePO4 /C sample was prepared via a carbothermal reduction process of calcining the obtained FePO4 ·2H2 O precursor with Li2 CO3 and glucose in N2 atmosphere. The re-synthesized LiFePO4 /C sample inherits the hierarchical microflower structure of the FePO4 ·2H2 O precursor, with a diameter of 1–2 μm. Electrochemical test indicates that the re-synthesized LiFePO4 /C shows excellent electrochemical performance as cathode material for lithium ion batteries. The discharge capacity can reach 159.3 mAh g −1 at 0.1C rate and 86.3 mAh g −1 even at 20C rate, respectively. After 500 cycles at 5C, they still can deliver a discharge capacity of 105 mAh g −1 with a high capacity retention rate of 95.4%. Moreover, the lithium element was also recovered in the form of LiH2 PO4 from the filtrate after collecting the FePO4 ·2H2 O precipitate. This work provides a promising route for large scale recovery and reuse of spent LiFePO4 cathode materials of lithium-ion batteries.